Self-care Behaviour of the Elderly with Heart Failure and its Associated Factors in Hospitals of Gonbad Kavus in 2018 - Saeed Eimer; Gholam Reza Mahmoodi-Shan (Golestan University of Medical Sciences, 2020)
Background: Heart Failure is a common chronic disease and the cause of the elderly's mortality worldwide. It has imposed a high financial burden on health systems and families. Self-care is an important aspect of nursing and treating such patients. The aim of this study was to determine the self-care behavior and its association with demographic and clinical factors in the elderly with heart failure. Methods: The cross-sectional study was conducted on 120 elderly patients with heart failure, admitted to Cardiology Wards of Khatam Al-Anbia, Shohada, and Payambar Azam Hospitals of Gonbad Kavus County in 2018. The convenience sampling method was used to recruit participants. For data collection the Miller Self-care Behaviour Scale and the elderly's demographic information checklist were used. Data were presented in descriptive statistics, and analyzed using ANOVA, independent t-test and Spearman's correlation test in SPSS ver 16. The significant level was used p<0.05. Results: The self-care scores of patients were 66.08 ±8.44. The Self-care Behaviour scores were 68.25±1.01 and 64.12±0.7 in women and men respectively (p=0.004). There were no significant correlations between the scores of self-care with ejection fraction percentages and education levels. Conclusions: The score of self-care in the elderly with heart failure were low. Therefore, the self-care of the elderly with heart failure should be improved by training.